Analysis of Factors Affecting Satisfaction and Repurchase Intent at Coffee Shops in Bogor Regency - Krisyanti, Yosi; Indrajaya, Sonny (Dinasti Publisher, 2024)
This research aims to determine the factors that influence coffee shop consumers in Bogor Regency. This research was conducted using quantitative methods. The population is coffee shop consumers in Bogor Regency whose exact number is unknown. The sample in this study was 225 consumers of medicinal coffee shops. The questionnaire presents statements that resp ondents must choose from strongly agree to strongly disagree on a scale of 1-5 points. Hypothesis testing uses Structural Equation Model Wrap PLS. The results of hypothesis testing show that the relationship between variables is related and significant, both directly and through mediation.